1998
DOI: 10.1093/jac/42.6.831
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation rates, stabilities, cytotoxicities and release of liposomal tetracycline and doxycycline in human serum [In Process Citation]

Abstract: Tetracycline and doxycycline were encapsulated in cationic, anionic and neutral liposomes. The amounts of antibiotic encapsulated, the stability of each preparation at 4 degrees C for 4 weeks, and the kinetics of the release of entrapped drug into human sera were assessed by high-performance liquid chromatography. The toxicities of the liposome preparations on human erythrocytes and HeLa 229 cells were evaluated in vitro. The results showed that doxycycline was entrapped more efficiently than tetracycline, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…In the initial experiments, persistent cultures were exposed to doxycycline concentrations ranging from 0.05 to 50 g/ml. In these experiments, it was observed that exposure to doxcycline concentrations above 20 g/ml for 48 h was toxic to HeLa cells, consistent with previous observations with other mammalian cell lines (19,41). Doxycycline, at a concentration of 1 g/ml, was used alone or in combination with 0.2 mM L-1MT in the experiments reported here.…”
Section: Methodssupporting
confidence: 91%
“…In the initial experiments, persistent cultures were exposed to doxycycline concentrations ranging from 0.05 to 50 g/ml. In these experiments, it was observed that exposure to doxcycline concentrations above 20 g/ml for 48 h was toxic to HeLa cells, consistent with previous observations with other mammalian cell lines (19,41). Doxycycline, at a concentration of 1 g/ml, was used alone or in combination with 0.2 mM L-1MT in the experiments reported here.…”
Section: Methodssupporting
confidence: 91%
“…With the cell line HeLa 229 and the MGG staining method, the present study obtained low MIC values with liposomeencapsulated Tet and Dox which are close to glycylcycline anti-chlamydia1 activities [23]. Studies on the pharmacokinetics and in-vitro toxicity of these liposome-encapsulated drugs performed in this laboratory have shown that they have different patterns of stability in human serum but are not toxic for human erythrocytes and HeLa 229 cells in culture [24]. These results demonstrate that liposomal Tet and Dox could be very useful as an alternative strategy for antimicrobial therapy.…”
Section: Discussionsupporting
confidence: 52%
“…At present, the most extensively investigated nonviral vector is cationic liposomes. They have been successfully used to deliver genes, proteins, oligonucleotides and antibiotics in several cell types [35,36,37]. They can provide slow release of encapsulated drugs, which lead to prolonged exposure to tumor cells and enhanced antitumor efficacy [38].…”
Section: Discussionmentioning
confidence: 99%